Quality of life of patients with cervicogenic headaches = Jakość życia pacjentów z bólem głowy pochodzenia szyjnego - Kocjan, Janusz (Journal of Education, Health and Sport, 2016)
Kocjan Janusz. Quality of life of patients with cervicogenic headaches = Jakość życia pacjentów z bólem głowy pochodzenia szyjnego. Journal of Education, Health and Sport. 2016;6(1):138-146. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45134 http://ojs.ukw.edu.pl/index.php/johs/article/view/45134 https://pbn.nauka.gov.pl/works/703653 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 20.01.2016. QUALITY OF LIFE OF PATIENTS WITH CERVICOGENIC HEADACHES Jakość życia pacjentów z bólem głowy pochodzenia szyjnego Janusz Kocjan Medical University of Silesia, School of Medicine, Katowice, Poland Abstract Introduction: Although the quality of life has been investigated in a numerous of previous studies, still is little known about this topic among patients with cervicogenic headache diagnosis. Aim of the study: To assess QoL in CGH group and to explore the relationship of QoL to selected demographic and medical variables. Material and methods: A total of 47 patients with cervicogenic headache were examined. On average, participants were 47,21 years old and 55,3% was female. To evaluate a quality of life the WHOQOL-BREF questionnaire was used. Results: Means and standard deviations in each domain were as follows: DOM1=10,04±3,07; DOM2=14,49±2,88; DOM3=16,59±3,12; DOM4=15,80±2,85. The highest mean values were noted in following items: Q25 (transport; M=4,46), Q11 (body appearance; M=4,33) and Q13 (vailability of information; M=4,31). The lowest scores concerned Q3 (pain; M=1,86), Q4 (dependence on medical treatment; M=1,94) and Q10 (energy; M=2,07). Differences in QoL due to age, sex and selected medical variables were observed. Relationship of QoL to education level, marital status and local residence were also found. Conclusions: The present study supports the hypothesis that quality of life impairment is likely to be present in clinical samples of CGH and is directly associated with duration time of CGH and number of CGH incidence during day. Keywords: quality of life, QoL, WHOQOL-BREF, cervicogenic headaches.